Elementi križa u Misi Leonarda Bernsteina - Čačić, Antonia; Brđanović, Davor (2021)
U kontekstu analize dramske radnje glazbeno–scenskoga djela Misa, kazališni komad za pjevače, svirače i plesače Leonarda Bernsteina, razmatranja razloga proturječnih tumačenja te propitivanja postojanja elemenata svetogrđa i umjetničke vrijednosti toga djela — članak promišlja razumijevanje umjetnosti, kriterije tumačenja umjetničkoga djela, pitanje odnosa stvaranja i destrukcije, kao i dekadencije i kiča u umjetnosti. Putem različitih glazbenih stilova i provokativnoga dijaloga, koji uvelike prelazi okvire teksta katoličkoga bogoslužja, u raspletu dramske radnje Bernsteinova Misa dovodi protagoniste do katarze. Unatoč krizi povjerenja u svjetovne i vjerske autoritete i institucije te dubokoj moralnoj krizi američkoga društva 70–ih godina 20. stoljeća, koja je do danas dosegnula globalne razmjere, Bernstein ne gubi nadu i vjeru u mogućnost pročišćenja i pozitivne promjene svijesti pojedinca i društva.
This paper analyses a musical theatre piece by Leonard Bernstein titled, "Mass: A Theatre Piece for Singers, Players, and Dancers". Aside from an analysis of the dramatic content of the "Mass", the paper discusses some general aesthetic and artistic criteria, the reasons for contradictory interpretations of the piece, the presence of sacrilegious features, the justification of the presence of elements that ironize some features of religious life, the artistic value of the piece, criteria for evaluating art and the use of elements with shock value. Through various musical styles and a provocative dialogue that goes beyond the framework of Catholic liturgy, "Mass" leads the protagonists to a catharsis in the dramatic unfolding of the action. With the help of cathartic elements, called "elements of the cross", there develops a compositional about–turn in the direction of nothingness, such that the possibilities of human choice are more clearly delineated. The intent of the work, evident in the synthesis, was to show that Bernstein"s artistic treatment of potentially sacrilegious and ironic elements is justified as artistic expression, i.e., the truth was transcended by means of these features and through artistic expression. By combining atheistic views with artistic persuasiveness, Bernstein pointed to the crisis of faith in the USA in the 1970"s. Despite this crisis, he loses neither hope nor faith in the possibility of purification and a positive change in the individual"s consciousness and that of society.
Bibliografija: 22 jed.
Sažetak ; Summary.
Keywords: Bogoslužje -- Dekadencija -- Estetika -- Glazba; Bernstein, Leonard